Development of a pharmacy practice intervention: lessons from the literature - Hughes, Carmel M. (Int J Clin Pharm, 2015)
The development of health interventions is receiving increasing attention within the scientific literature. In the past, interventions were often based on the ISLAGIATT principle: that is, ‘It seemed like a good idea at the time’. However, such interventions were frequently ineffective because they were either delivered in part or not at all, demonstrating a lack of fidelity, or because little attention had been paid to their development, content, and mode of delivery. This commentary seeks to highlight the latest methodological advances in the field of intervention development, drawing on health psychology literature, together with guidance from key organisations and research consortia which are setting standards for development and reporting. Those working within pharmacy practice research can learn from the more systematic approach being advocated, and apply these methods to help generate evidence to support new services and professional roles.